1)2b+2c-2d
2)-3b+3c-3d
3)-5b-5c+5d
4)4b-4c+4d
Пошаговое объяснение:
Объяснять тут нечего, просто умножаете число перед скобками на буквы в скобках, учитывая знаки.
1) 2 ∗ (b + c - d)=2b +2c - 2d
2) − 3 ∗ (b − c + d)=-3b +3 c - 3d
3) − 5 ∗ (b + c − d)=-5b - 5c +5 d
4) 4 ∗ (b − c + d)=4b − 4c +4d
1)2b+2c-2d
2)-3b+3c-3d
3)-5b-5c+5d
4)4b-4c+4d
Пошаговое объяснение:
Объяснять тут нечего, просто умножаете число перед скобками на буквы в скобках, учитывая знаки.
Пошаговое объяснение:
1) 2 ∗ (b + c - d)=2b +2c - 2d
2) − 3 ∗ (b − c + d)=-3b +3 c - 3d
3) − 5 ∗ (b + c − d)=-5b - 5c +5 d
4) 4 ∗ (b − c + d)=4b − 4c +4d